Estimation of miRNA 208 Effects in Inducing Epithelial-Mesenchymal Transition by Targeting CDH2 in Breast Cancer Patients of Iraqi Population - Salih, Arwa M.; Aziz, Ismail H.; Mohsin, Forat Yahya (Iraqi Journal of Science, 2025)
Breast cancer is the most frequently diagnosed disease in women and remains a leading cause of cancer-related deaths worldwide. The small non-coding RNA molecule, MicroRNA-208 (miR-208), plays a crucial role in the development and advancement of numerous malignancies, including breast cancer. This study aimed to investigate miR-208 potential as an oncogene in breast cancer by examining its impact on cell motility and epithelial-mesenchymal transition (EMT). Tissue samples from 25 Iraqi women with malignant breast cancer and 25 with benign breast cancer were analysed. Total RNA was extracted from the samples and real-time reverse transcription-polymerase chain reaction (RT-PCR) was performed using SYBR Green technology to measure miR-208 expression levels. Tissue samples from both benign and malignant tumours were analysed to determine U6 gene expression. The analysis showed that the typical Ct values for benign and malignant samples were 29.83 and 29.67 respectively. No significant difference in U6 expression levels was detected between benign and malignant tumours. However, upon comparing the initial malignant and the benign tumours samples, miRNA-208 ΔΔCT values were found to be substantially lower (-7.105 and -0.781 respectively) with a p-value of less than 0.05. The study found that malignant tumours had a significantly higher miRNA-208 folding value (2.896±) compared to benign tumours which had substantially lower miRNA-208 folding values (1.591 ±0.37). The study also found that the differences were statistically significant (p-value = 1.292*). In conclusion, the study found evidence linking miR-208 to the CDH2 gene, indicating its role in the development and susceptibility to breast cancer in certain Iraqi women.